Perancangan Perangkat Lunak Sertifikasi Pembimbing Manasik Haji Dengan Extreme Programming - Agus Pamuji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The certification of the Hajj rituals supervisor is a legal acknowledgment of the ability and expertise in guiding the Hajj rituals. In this study, discusses designing a system that can be applied to the implementation of certification. The certification implementation is carried out online by the Regional Office (Kanwil) of the West Java Ministry of Religion. The previous condition was that the activities of implementing the certification for the Hajj ritual supervisors were carried out offline (face to face). Given that the pandemic has hit and is full of risks, if it continues, the alternative policy is to use the online method. At the beginning of the implementation of online certification, there were problems. The main obstacle is the inefficiency and effectiveness of the factors of time, speed and relevance in the delivery of communication and information. Thus, the proposed system is generated through a website-based platform and is run online. The research method uses the Extreme Programming approach. The Extreme Programming consists of planning, designing, coding, and testing. The proposed system is run on a web-based platform whose program code is written in PHP and uses MySQL as a database data processor (RDBMS). Furthermore, the tools that are applied in system design use UML (Unifed modeling language). This research resulted in a Web-Based design of an Information System for Hajj pilgrimage mentoring certification which can simplify the certification implementation process, as well as simplify the presentation of certification data and its processing. Based on the results of testing using the Black-box method, the system can be implemented properly, while the PIECES analysis presents changes when the new system is implemented in the implementation of certification. The results of the design of the certification information system have proven to be effective. The design of this system can overcome the weakness of the implementation of certification to be more accurate.